Productive government expenditure and economic growth - Andreas Irmen; Johanna Kuehnel (Center for Economic Studies and ifo Institute (CESifo), 2008)
We provide a comprehensive survey of the recent literature on the link between productive government expenditure and economic growth. Starting with the seminal paper of Robert Barro (1990) we show that an understanding of the core results of the ensuing contributions can be gained from the study of their respective Euler equations. We argue that the existing literature incorporates many relevant aspects, however, policy recommendations tend to hinge on several knife-edge assumptions. Therefore, future research ought to focus more on idea-based endogenous growth models to check the robustness of policy recommendations. Moreover, the inclusion of hitherto unexplored types of government expenditure, e. g., on the rule of law, would be desirable.
Keywords: E62; H10; H21; H41; H54; O41; 330; economic growth; government expenditure; public goods; fiscal policy; Öffentliche Ausgaben; Öffentliches Gut; Produktivität; Neue Wachstumstheorie; Finanzpolitik; Wirtschaftspolitische Beratung; Theorie